Desenvolvimento de modelo de diagnóstico para avaliação do grau de maturidade em cultura de segurança ambiental nos ambientes de trabalho - Alves, Andréia Mariano [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
The present work aims to develop methods for measuring the maturity of safety culture in work environments in the branch of the textile industry, to characterize and identify the potential hazards and risks of accidents at work, and to identify the main factors that allow assessing over there. Research Methodology / Procedures The method chosen to carry out the present work was the exploratory and descriptive case study, which comprises planning, data collection techniques and data analysis approaches, which aims at the closest access with the studied subject and offers more detailed information about it, facilitating the delimitation of the subject for the study and contributing to deepen the preliminary concepts through the qualitative approach of the problems of a company in the branch of the textile industry. In this study, the degrees of maturity of the environmental safety culture will be evaluated in the case studies of a textile company in the interior of the city of São Paulo. Define culture and conceptualization of maturity, culture and organizational climate and work safety. To study the existing models in academic research on the implementation of management systems and culture of work safety and organizational culture. Results and Discussions Companies in the textile industry have always had low levels of effectiveness in relation to the maturity of the safety culture at work, which involve more than removing hazards and creating safety procedures. However, it proposes training, motivation and engagement on the part of managers and workers, and for this to be effective, it is necessary to involve, motivate and work people to change their attitudes, behaviors and thoughts, thus improving their ability to understand the situation. A culture of lasting safety can be the accident prevention process, respecting and knowing rules and regulations is essential for success, decreases losses and damages. Managerial Implications It is essential to have a consistent and gradual roadmap that guides teams towards protecting the greatest asset of any organization: its employees. Continuously improve the quality of communication and disseminate the standards that workers must comply with, more clearly among managers and employees. It is important to do this through meetings, the bulletin board or even by e-mail, or find the best alternative to raise awareness among everyone belonging to the organization. Compliance with safety standards can be more complicated for some employees than for others. It is extremely important that the company offers training for employees. viii Conclusions and Limitations of the Research As limitations, the difficulty of convincing on the part of the company and willingness to make available the evaluations that the present work proposed, this study focused more on the identification of the factors to measure the safety culture present in the questionnaire, seen that in Brazil this is the most used instrument. However, it would be convenient to verify that other instruments of data collection that are used to verify the safety culture during the development of the research, it was possible to perceive the evolution that the theme has been receiving in the work philosophies in the studied periods, perhaps due to the continuous disinterest on the part of companies in investing in work safety, and the growing cases of major accidents that have been occurring in recent years Originality One of the most interesting factors in work safety is that it can be improved over time. It is for this reason that you must give autonomy to all employees to contribute with their knowledge and experiences acquired in the sector. Promoting safety at work requires everyone's commitment. It is the individual care of each employee that, in the end, will make the company develop the safe environment that professionals will enjoy now and in the future. Keywords: Organizational Culture, Organizational Climate, Workplace Safety, Risk Management, Environmental Risk Agents.

O presente trabalho, tem por objetivo desenvolver métodos de mensuração de maturidade de cultura de segurança nos ambientes de trabalho no ramo da indústria têxtil, caracterizar e identificar os potenciais de perigos e riscos de acidentes de trabalho, e identificar os principais fatores que permitem avaliá-la. Metodologia / Procedimentos de Pesquisa O método escolhido para a realização do presente trabalho, foi o estudo de caso exploratório e descritivo, que compreende o planejamento, as técnicas de coleta de dados e as abordagens de análise dos dados, que visa o acesso mais próximo com o tema estudado e oferece informações mais detalhadas sobre o mesmo, facilitando a delimitação do assunto para o estudo e contribuindo para aprofundar os conceitos preliminares através da abordagem qualitativa das problemáticas de uma empresa no ramo da indústria têxtil. Neste estudo serão avaliados os graus de maturidade da cultura de segurança ambiental no trabalho de estudos de casos de uma empresa têxtil no interior da cidade de São Paulo. Definir de cultura e conceituação de maturidade, de cultura e clima organizacional e segurança do trabalho. Estudar os modelos existentes nas pesquisas acadêmicas sobre a implementação de sistemas de gestão e cultura de segurança do trabalho e da cultura organizacional. Resultados e Discussões As empresas no ramo da indústria têxtil, sempre tiveram baixos índices de efetividade em relação a maturidade da cultura de segurança do trabalho os quais envolvem mais do que remover os perigos e criar procedimentos de segurança. Contudo, propõe a capacitação, motivação e engajamento por parte dos gestores e trabalhadores, e para isso ser efetivo é necessário envolver, motivar e trabalhar as pessoas para mudar suas atitudes, seus comportamentos e pensamentos, melhorando assim, suas capacidades de compreensão da situação. Uma cultura de segurança duradoura pode ser o processo de prevenção de acidentes, respeitar e conhecer normas e regulamentos é primordial para o êxito, diminui perdas e danos. Implicações Gerenciais É indispensável que haja um roteiro, consistente e gradativo, que guie as equipes em direção à proteção do maior patrimônio de qualquer organização: seus funcionários. Melhor continuamente a qualidade da comunicação e divulgar as normas que os trabalhadores devem cumprir, com mais clareza dentre os gestores e colaboradores. É importante fazer isso por meio de reuniões, do mural de recados ou até mesmo por e-mail, ou encontrar a melhor alternativa pra sensibilizar a todos pertencentes a organização. O cumprimento das normas de segurança pode ser mais complicado para uns colaboradores do que para outros. É de extrema relevância que a empresa ofereça treinamento para os funcionários. viii Conclusões e Limitações da Pesquisa Como limitações, a dificuldade de convencimento por parte da empresa e disposição a se colocar disponível as avaliações que o presente trabalho propunha, este estudo focou mais na identificação dos fatores para mensurar a cultura de segurança presentes no questionário, visto que no Brasil este é o instrumento mais utilizado. No entanto, seria conveniente verificar que outros instrumentos de coleta de dados que são utilizados para verificar a cultura de segurança durante o desenvolvimento da pesquisa, foi possível perceber a evolução que a temática vêm recebendo nas filosofias de trabalho nos períodos estudados, talvez seja pelo contínuo desinteresse por parte das empresas em investir na segurança do trabalho, e o crescente casos de acidentes de grande porte que vêm ocorrendo nos últimos anos Originalidade Um dos fatores mais interessantes da segurança do trabalho é que ela pode ser aprimorada com o tempo. É por esse motivo que você deve dar autonomia para todos os colaboradores contribuírem com seu conhecimento e experiências adquirida do setor. A promoção da segurança no trabalho exige comprometimento de todos. É o cuidado individual de cada colaborador que, no final das contas, fará com que a empresa desenvolva o ambiente seguro do qual os profissionais desfrutarão no presente e no futuro. Palavras-chaves: Cultura Organizacional, Clima Organizacional, Segurança do Trabalho, Gerenciamento de riscos, Agentes de riscos ambientais.
Development of diagnostic model for assessing the degree of maturity in environmental safety culture in work environments
Keywords: cultura organizacional; clima organizacional; segurança do trabalho; gerenciamento de riscos; agentes de riscos ambentais